Nucleic Acid Chaperone Activity of the ORF1 Protein from the Mouse LINE-1 Retrotransposon - Martin, Sandra L. (American Society for Microbiology, 2001)
Non-LTR retrotransposons such as L1 elements are major components of the mammalian genome, but their mechanism of replication is incompletely understood. Like retroviruses and LTR-containing retrotransposons, non-LTR retrotransposons replicate by reverse transcription of an RNA intermediate. The details of cDNA priming and integration, however, differ between these two classes. In retroviruses, the nucleocapsid (NC) protein has been shown to assist reverse transcription by acting as a “nucleic acid chaperone,” promoting the formation of the most stable duplexes between nucleic acid molecules. A protein-coding region with an NC-like sequence is present in most non-LTR retrotransposons, but no such sequence is evident in mammalian L1 elements or other members of its class. Here we investigated the ORF1 protein from mouse L1 and found that it does in fact display nucleic acid chaperone activities in vitro. L1 ORF1p (i) promoted annealing of complementary DNA strands, (ii) facilitated strand exchange to form the most stable hybrids in competitive displacement assays, and (iii) facilitated melting of an imperfect duplex but stabilized perfect duplexes. These findings suggest a role for L1 ORF1p in mediating nucleic acid strand transfer steps during L1 reverse transcription.